Combining theory and experiment for X-ray absorption spectroscopy and resonant X-ray scattering characterization of polymers. (2nd September 2016) - Su, Gregory M.; Cordova, Isvar A.; Brady, Michael A.; Prendergast, David; Wang, Cheng
Abstract: An improved understanding of fundamental chemistry, electronic structure, morphology, and dynamics in polymers and soft materials requires advanced characterization techniques that are amenable to in situ and operando studies. Soft X-ray methods are especially useful in their ability to non-destructively provide information on specific materials or chemical moieties. Analysis of these experiments, which can be very dependent on X-ray energy and polarization, can quickly become complex. Complementary modeling and predictive capabilities are required to properly probe these critical features. Here, we present relevant background on this emerging suite of techniques. We focus on how the combination of theory and experiment has been applied and can be further developed to drive our understanding of how these methods probe relevant chemistry, structure, and dynamics in soft materials. Graphical abstract: Highlights: X-ray absorption spectroscopy and resonant scattering enhance contrast in soft matter. Soft X-ray spectroscopy combined with theory elucidates chemical bonding details. XAS and RSoXS are ideally suited for in situ and operando studies. X-ray photon correlation spectroscopy probes time-resolved structural changes.